Higher C-reactive protein to high-density lipoprotein cholesterol ratio is associated with hyperuricemia in diabetes and prediabetes: a cross-sectional study - Huang, Dongni; Ma, Jing; Zhao, Yan; Pan, Qi; Xu, Guogang; Guo, Lixin (Frontiers in Endocrinology, 2025)
BackgroundThe ratio of C-reactive protein to high-density lipoprotein cholesterol (CRP/HDL-c) reflects systemic inflammation and lipid status, both of which are implicated in uric acid metabolism. This study aimed to investigate the association between CRP/HDL-c and the prevalence of hyperuricemia (HUA) among adults with diabetes or prediabetes.MethodsThis cross-sectional study included 10915 adults with diabetes or prediabetes from the Health Management Institute of the PLA General Hospital. Hyperuricemia was defined as a serum uric acid concentration ≥7 mg/dL in men and ≥6 mg/dL in women. Participants were divided into quartiles according to the ratio. Multivariate logistic regression and restricted cubic spline analyses were used to assess associations. Subgroup analyses and interaction tests were performed.ResultsThe prevalence of HUA increased across CRP/HDL-c quartiles (18.43%, 20.39%, 24.54%, and 29.82%; P < 0.001). Higher CRP/HDL-c levels were independently associated with increased HUA risk (odds ratio [OR] = 1.64, 95% confidence interval [CI]: 1.14–2.36; P = 0.008). Participants in the highest quartile had a significantly higher risk compared to those in the lowest quartile (OR = 1.33, 95% CI: 1.15–1.54; P < 0.001). The association was stronger in females (OR = 1.30) than in males (OR = 1.14), with a significant gender interaction (P for interaction = 0.031). Among females, the association was more pronounced in those aged <50 years (OR = 1.47). RCS analysis indicated a linear dose–response relationship.ConclusionsAn elevated C-reactive protein to high-density lipoprotein cholesterol ratio is significantly associated with a higher risk of hyperuricemia in adults with diabetes or prediabetes, particularly in younger females.